PRIMARY-HF: Heart Failure Screening in Primary Care using Point-of-Care - Jonathan dos Santos; João Pedro Nobre; João Pedro Ferreira; Maria Inês M. Marques; Miguel Henriques; Nuno Cardim; Tiago Villanueva; Alexandra Gonçalves (Acta Médica Portuguesa)
Introduction: Heart failure is a major health challenge with high morbidity and socioeconomic burden, especially when diagnosis is delayed. In primary care, HF detection can be challenging due to symptoms overlapping with other conditions, limited access to diagnostic tools, and resource constraints. This study explores the use of natriuretic peptides (NT-proBNP) and point-of-care ultrasound (POCUS) with artificial intelligence integration as tools to improve HF screening and management in primary care. This study aims to determine whether NT-proBNP testing alone or combined with cardiac POCUS improves heart failure diagnosis and management in primary care settings, and to evaluate the cost-effectiveness of this approach. Methods: This randomized controlled trial will involve patients aged 50 or older with suspected HF or cardiovascular risk factors, recruited across four primary care centers. Participants will be randomly assigned to one of four groups: standard of care (SoC), SoC with NT-proBNP, SoC with NT-proBNP and POCUS, and SoC with POCUS. Primary outcomes include new HF diagnosis, initiation of guideline-directed medical therapy, and improvement in health-related quality of life. Secondary outcomes include cost-effectiveness and the quality assessment of POCUS performed by trained primary care physicians. The integration of NT-proBNP and POCUS in primary care may enhance early heart failure diagnosis, optimize therapy, improve patient quality of life, and reduce healthcare costs associated with heart failure misdiagnosis and delayed treatment. This study could support the broader adoption of accessible diagnostic tools to improve heart failure management in primary care.